2017
DOI: 10.1680/jgeot.15.p.112
|View full text |Cite
|
Sign up to set email alerts
|

Interface shear box tests for assessing axial pipe–soil resistance

Abstract: The clay-interface shear resistance is an important parameter for the design of offshore pipelines, which slide on the seabed as a result of thermally-induced expansion, contraction and lateral buckling. This paper presents a methodology for characterising the clay-interface resistance and quantifying the effect of drainage and consolidation during or in between shearing episodes. Models for describing the clay-interface resistance during planar shearing are presented and compared to test data for a range of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(15 citation statements)
references
References 33 publications
2
10
0
2
Order By: Relevance
“…In order for the shallow penetrometers to be able to measure the drained friction angle during slow sustained rotation, the penetrometer surface must be sufficiently rough. To identify a suitable surface finish, low stress drained interface shear box tests (σ'n ∼8-12 kPa; 82 mm diameter interface; see also Boukpeti & White, 2017) were conducted on normally consolidated kaolin clay using machined and shot-blasted plastic inserts (Polyoxymethylene).…”
Section: Interface Finishmentioning
confidence: 99%
“…In order for the shallow penetrometers to be able to measure the drained friction angle during slow sustained rotation, the penetrometer surface must be sufficiently rough. To identify a suitable surface finish, low stress drained interface shear box tests (σ'n ∼8-12 kPa; 82 mm diameter interface; see also Boukpeti & White, 2017) were conducted on normally consolidated kaolin clay using machined and shot-blasted plastic inserts (Polyoxymethylene).…”
Section: Interface Finishmentioning
confidence: 99%
“…Studies on the shear behavior of bimaterial interfaces between soil and concrete, steel, geotextiles, and other manufactured materials, especially under low normal stresses ( σ n = 1–100 kPa), are abundant in the literature (e.g., Boukpeti & White, ; Eid et al, ; Ganesan et al, ; Ho et al, ; Lemos & Vaughan, ; Potyondy, ; Tsubakihara & Kishida, ; Wijewickreme et al, ; Zhang & Zhang, ). Equally, in fault mechanics, many researchers have been focusing on the slip‐ and rate‐dependent behavior of rock interfaces and thin gouge layers under high normal stresses ( σ n = 1–20 MPa) to understand the behavior of faults under subseismic and coseismic slip rates (e.g., Di Toro et al, , , ; Hirose & Shimamoto, ; Perfettini & Ampuero, ; Kitajima et al, ; Togo et al, ; Yao et al, , Ma et al, ; Yao et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Figure 18 shows a schematic representation of the influence of shearing rate on the strength of normally consolidated clay, according to Quinn et al 66 . It was observed that, in soil‐on‐soil or interface shear tests, when increasing the shear rate, the drainage condition shifts progressively from “drained” with the volumetric change, to “partially drained” with slight volumetric change and to “undrained” with no volumetric change in the localized shear zone 67,68 . Under experimental CNL condition, the total normal stress is kept constant, while the effective normal stress evolves differently due to the generation of excess pore‐water pressures under different shearing rates.…”
Section: Discussionmentioning
confidence: 99%